Navigating Cardiovascular Risk and Lipid Management in Indian Patients: Key Messages from the Lipid Association of India 2024 Consensus Statement IV - Puri, Raman; Mehta, Vimal; Bansal, Manish; Shetty, Sadanand; Yusuf, Jamal; Agarwala, Rajeev; Vijan, Vinod Madan; Muruganathan, Arumugam; Tiwaskar, Mangesh; Narasingan, Sanjeevi Nathamuni; Iyengar, Shamanna Seshadri (Journal of the Association of Physicians of India, 2024)
Effective lipid management is crucial for preventing atherosclerotic cardiovascular disease (ASCVD). The Western lipid guidelines may not apply to Indian subjects because of the vast differences in cardiovascular (CV) disease epidemiology. To overcome this challenge, the Lipid Association of India (LAI) in 2016 proposed an ASCVD risk stratification algorithm. The appropriate low-density lipoprotein cholesterol (LDL-C) goals for various risk groups were proposed, with an LDL-C target of <50 mg/dL recommended for the first time globally for patients in the very high-risk group. Subsequently, in 2020, an extreme risk group was added because of observations that patients with more severe or extensive ASCVD, along with multiple risk factors and comorbidities, had increased rates of adverse CV events and could benefit from more intensive LDL-C lowering. The extreme risk group was subdivided into categories A and B, with LDL-C targets as low as 30 mg/dL or lower. The availability of further evidence regarding the significance of novel risk factors and the availability of new LDL-C lowering therapies necessitated refining the ASCVD risk assessment algorithm, defining LDL-C targets for subjects with these risk factors, and incorporating recommendations for attaining very low LDL-C levels in a defined, select group of patients. Accordingly, the LAI expert group recently published the Consensus Statement IV, which is a comprehensive document addressing several key issues about risk stratification and dyslipidemia management in Indian subjects. LDL-C and nonhigh-density lipoprotein cholesterol (non-HDL-C) are not only primary and co-primary targets for lipid-lowering therapy but also risk factors for ASCVD risk stratification. Apolipoprotein B is a secondary target. The risk assessment algorithm has been updated to incorporate several nonconventional yet relevant CV risk factors. Additionally, the role of subclinical atherosclerosis has been highlighted. The CV risk due to subclinical atherosclerosis has been considered equivalent to that of established ASCVD, and hence, similar LDL-C targets have been recommended. Furthermore, a new risk category-extreme risk group category C has been added for the small subgroup of patients who continue to experience ASCVD sequelae despite achieving LDL-C levels of 30 mg/dL or lower. An ultralow LDL-C target (10-15 mg/dL) has been recommended along with optimal control of risk factors and guideline-directed management of comorbidities. Dyslipidemia management should be effective with sustained LDL-C lowering. In high-risk situations (e.g., acute coronary syndrome), the LDL-C target should be achieved as early as possible, preferably within the first 2 weeks. The present document summarizes the key messages from the LAI Consensus Statement IV.